Isolation and identification of diosgenin and flavonoids compound from ethanol extract of Dioscorea hispida Dennst. tuber - syahputra, hafid; Masfria; Amana, Meuthia Rizka; Rivai, Muhammad (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
The tuber of Dioscorea hispida Dennst. has potential for development as a synthetic pharmaceutical ingredient due to the presence of secondary metabolites such as diosgenin and flavonoids, which exhibit biological activity within the body. Further exploration of this potential requires the isolation and identification of these compounds. Diosgenin was isolated from the ethanol extract using thin-layer chromatography, while flavonoids were isolated from the ethyl acetate fraction using paper chromatography. The pure isolates of both compounds were identified using UV-Vis spectrophotometry and FT-IR spectroscopy. The UV-Vis spectrophotometric analysis of diosgenin revealed maximum absorption wavelengths at 205 and 453 nm. Flavonoid isolates exhibited maximum absorption wavelengths of 264 nm for the first isolate, 265 nm for the second, 276 nm for the third, and 272 nm for the fourth. FT-IR spectroscopic analysis of the diosgenin isolate indicated the presence of functional groups such as -OH, aromatic C=C, and aromatic C-O, while the flavonoid isolate showed the presence of O-H, aromatic C-H, aliphatic C-H, C=O, C=C, and C-O. These identification results confirm that the isolates obtained indeed contain diosgenin and flavonoids.